Comprehensive classification of ABC ATPases and their functional radiation in nucleoprotein dynamics and biological conflict systems. Issue 18 (7th September 2020) - Krishnan, Arunkumar; Burroughs, A Maxwell; Iyer, Lakshminarayan M; Aravind, L
Abstract: ABC ATPases form one of the largest clades of P-loop NTPase fold enzymes that catalyze ATP-hydrolysis and utilize its free energy for a staggering range of functions from transport to nucleoprotein dynamics. Using sensitive sequence and structure analysis with comparative genomics, for the first time we provide a comprehensive classification of the ABC ATPase superfamily. ABC ATPases developed structural hallmarks that unambiguously distinguish them from other P-loop NTPases such as an alternative to arginine-finger-based catalysis. At least five and up to eight distinct clades of ABC ATPases are reconstructed as being present in the last universal common ancestor. They underwent distinct phases of structural innovation with the emergence of inserts constituting conserved binding interfaces for proteins or nucleic acids and the adoption of a unique dimeric toroidal configuration for DNA-threading. Specifically, several clades have also extensively radiated in counter-invader conflict systems where they serve as nodal nucleotide-dependent sensory and energetic components regulating a diversity of effectors (including some previously unrecognized) acting independently or together with restriction-modification systems. We present a unified mechanism for ABC ATPase function across disparate systems like RNA editing, translation, metabolism, DNA repair, and biological conflicts, and some unexpected recruitments, such as MutS ATPases in secondary metabolism.